House Prices, Money, Credit and the Macroeconomy. - Charles Goodhart; Boris Hofmann (European Central Bank (ECB), 2008)
This paper assesses the linkages between money, credit, house prices and economic activity in industrialised countries over the last three decades. The analysis is based on a fixed-effects panel VAR estimated using quarterly data for 17 industrialized countries spanning the period 1970-2006. The main results of the analysis are the following: (i) There is evidence of a significant multidirectional link between house prices, monetary variables and the macroeconomy. (ii) The link between house prices and monetary variables is found to be stronger over a more recent sub-sample from 1985 till 2006. (iii) The effects of shocks to money and credit are found to be stronger when house prices are booming. The last two results are, however, in general not statistically significant due to the large confidence bands of the impulse responses.
Keywords: E21; E22; E31; E32; E44; E47; E50; R21; R31; 330; collateral; financial liberalisation; House prices; money and credit; wealth effects; Immobilienpreis; Vermögenseffekt; Kreditmarkt; Finanzmarktregulierung; Welt